How significantly are principal and teacher entrepreneurial leadership related to teacher efficacy and organizational effectiveness in China? - Jinke, Li; Abdul Aziz, Nor Azni; Kadir, Suhaida Abdul (Frontiers in Education, 2025)
Entrepreneurial leadership has garnered increasing attention in educational contexts. While the positive impact of principals' entrepreneurial leadership on organizational advancement is well-documented, the role of teacher entrepreneurial leadership in organizational performance remains underexplored. This study aims to investigate the relationships among principal entrepreneurial leadership, teacher entrepreneurial leadership, teacher efficacy, and organizational effectiveness in Chinese schools. A quantitative research design was employed, utilizing structural equation modeling (SEM). Data were collected through paper-based questionnaires administered to 400 teachers in Shandong Province, China. Correlation and path analyses were conducted to examine the relationships between the variables. The findings reveal several significant relationships: principal entrepreneurial leadership is positively associated with teacher entrepreneurial leadership (β = 0.084, p < 0.01). Both principal entrepreneurial leadership (β = 0.512, p < 0.001) and teacher entrepreneurial leadership (β = 0.096, p < 0.001) are positively related to teacher efficacy. Similarly, both principal entrepreneurial leadership (β = 0.572, p < 0.001) and teacher entrepreneurial leadership (β = 0.159, p < 0.001) are positively related to organizational effectiveness. Additionally, teacher efficacy is positively associated with organizational effectiveness (β = 0.168, p < 0.001). This study provides a novel perspective on entrepreneurial leadership by examining the roles of both principals and teachers. The findings provide valuable insights for government educational policymakers, school principals, and teachers seeking to enhance organizational effectiveness and improve educational outcomes for the younger generation in China.